A legacy of lingering uncertainty: the experience of long-term cancer survivorship: a multiple-case study - Scott, Emma Joanne (2014)
More people are surviving cancer, and for longer. As a result, ‘cancer survivorship’ is a key policy and research issue. This exploratory study aimed to describe, and further understanding of, the cancer experience of individuals living five years or more post-treatment.